Pengharapan dalam Masa Pandemi Menurut Paus Fransiskus - Sefrianus Juhani (Sekolah Tinggi Widya Sasana, 2021)
This study aims to discover the concept of hope according to Pope Francis and how it is implemented in the context of the current pandemic. In an effort to obtain data on this theme, the author uses qualitative research, with the method of documentation. In this method, there are several stages that must be passed, namely the discovery of sources such as Church documents, books, journals, magazines, newspapers, and internet sources, especially the Vatican website, which discusses the theme being investigated by the author. After the data is collected, the next step is analysis. The existing data were analyzed in order to find common threads to construct the concept of hope from Pope Francis. Then the data is interpreted. The results of the interpretation are narrated and used to produce an article. The result obtained from this research is the discovery of the concept of hope, which is typical of Pope Francis. Its peculiarity lies in the notion of hope, the biblical basis that is used as a reference, the sources and objects of hope, the way to obtain hope. The concept of hope is very suitable to be applied in the current situation, namely the COVID-19 pandemic.